Perceptions among Antenatal Mother for Birth Preparedness and Complication Readiness: A Hospital Based Survey - Swati Matwaya; Kamlesh Malik; Sunita Kumari; Shaveta Jain; Kusum Rohilla (Medsci Publications, 2021)
Introduction: Preparing future mothers for the birth of newborn is an important part of birth preparedness counseling and one of major responsibility of health care provider. Objectives: The aim of this study was to assess awareness of antenatal mothers for birth preparedness and complication readiness and find association of awareness with socio demographic variables. Methodology: This descriptive study was conducted using cross sectional research design. Total 200 antenatal mothers were selected using the purposive sampling technique who was attending antenatal OPD at Pt. B. D. Sharma PGIMS, Rohtak, and Haryana, India. Data was collected by using semi structured questionnaire. Result: The majority of antenatal mothers were belongs to age group of 18-25 years and were secondary level educated. Most of antenatal mothers (54%) had poor knowledge of birth preparedness and complication readiness. Chi square test showed a significant association among awareness level of antenatal mothers with age (0.002*), educational level of self (0.003*) and husband (0.000*), gravida (0.03*), time to reach to health care facility (0.015*) and mode of transportation in emergency (0.005*). Odd ratios showed that antenatal mother who did not done their antenatal register had a 0.81 times more chances for less awareness than registered mothers. Conclusion: Awareness of antenatal mothers for birth preparedness and complication readiness was poor. There are various hindering factors which must be explored for betterment of maternal outcome and success of birth preparedness and complication readiness programs.